(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Augmented Reality has become an important tool for improving how students learn complex science lessons. In many schools, instructional materials are often limited, outdated or not suited for interactive teaching. This affects subjects such as Earth Science where learners need clear visual explanations to understand processes inside the Earth. Teachers often rely on drawings and verbal descriptions which may not show the full structure or behaviour of natural events. Studies have also shown that inadequate learning resources contribute to lower academic performance, which highlights the need for better teaching tools. EsAR was developed as a response to these challenges. It is a Markerless AR application that presents 3D volcano models, types of volcanoes and simple eruption simulations. By using a mobile device, learners can view these models in real space and see how volcanoes form and erupt. This makes abstract ideas easier to understand. Modern AR systems such as EasyAR use surface detection and SLAM to track the environment, which allows digital models to blend naturally with the physical world. The application was created using the Waterfall Model. Each step, from gathering requirements to deployment, was completed in sequence. Unity 3D and C# were used to build the models and interactions. Storyboard and interface designs ensured the app remained simple and accessible to users. The system was evaluated using selected ISO 25010 quality characteristics. IT experts, science teachers and students rated functional suitability, usability, reliability, performance efficiency, compatibility and portability. The overall rating of 3.77, interpreted as Excellent, showed that the application worked as intended and was easy to use on different devices. The results show that AR can help address gaps in science education. EsAR offers a practical way to improve visual understanding and make learning more engaging. With further development, AR can continue to support better science instruction in schools.